2020
DOI: 10.1177/0969733020948107
|View full text |Cite
|
Sign up to set email alerts
|

Forced treatment and care in home-dwelling persons with dementia

Abstract: Background: The use of forced treatment and care of home-dwelling persons with dementia is a universally important topic. These patients are completely dependent on care from others to continue living at home. Aim: This study aimed to gain insights into formal decisions related to the forced treatment and care of home-dwelling persons with dementia. Design and sample: This is a cross-sectional study, based on formal decisions of forced treatment and care of home-dwelling persons with dementia in Norway between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Subsequently, the ward personnel discussed whether they should apply for a coercive decree (a formal decision of forced treatment and care, sent to the County Governor's Office, cf. Gjellestad. et al, 2021).…”
Section: Avoiding Coercionmentioning
confidence: 99%
“…Subsequently, the ward personnel discussed whether they should apply for a coercive decree (a formal decision of forced treatment and care, sent to the County Governor's Office, cf. Gjellestad. et al, 2021).…”
Section: Avoiding Coercionmentioning
confidence: 99%
“…From previous research we know that the reported use of forced treatment to care for persons with dementia in home health care is low and there is little knowledge about how health professionals face situations of resistance [ 3 ]. The prevalence of forced treatment and care found in international studies show considerable variation [ 12 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“… Harmful interventions : In order to mitigate first‐order risks such as level of care needed by the client, their home environment and behaviours, homecare workers' skill levels and working conditions a range of interventional actions were described that had the potential to result in adverse care. These were the use of physical and chemical restraints and non‐consensual care (Gjellestad et al, 2020; Hamers et al, 2016; Leverton, Burton, Beresford‐Dent, Rapaport, Manthorpe, Mansour, et al, 2021b; Mengelers et al, 2018, 2020; Moermans et al, 2018); reduction of formal care provision, such as shorter visits when technology had been introduced or when homecare workers were fearful of violence (Fæø et al, 2020; Galinsky et al, 2010; Mole et al, 2019), and paternalism which was employed to manage conflict (Smebye et al, 2016). Beneficial interventions : Homecare workers adapted their approach to improve clients' wellbeing, reduce clients' anxiety, support them to feel safer and to work more effectively with family carers.…”
Section: Resultsmentioning
confidence: 99%
“…Homecare workers were also affected by second‐order risks, for example, when regulatory codes constrained person‐centred care (Lundberg, 2017) or ethical dilemmas became apparent (Gjellestad et al, 2020; Leverton, Burton, Beresford‐Dent, Rapaport, Manthorpe, Mansour, et al, 2021b; Smebye et al, 2016). Homecare workers had to cope with fear of violence (Galinsky et al, 2010), exhaustion, isolation (Yeh et al, 2018), their own emotional responses (Yeh et al, 2018), losses to professional integrity (Abrams et al, 2019), and/or loss of clients (Mole et al, 2019).…”
Section: Resultsmentioning
confidence: 99%